Financial Literacy and Mobile Banking Usage: The Moderating Role of Demographic Characteristics - Almanaseer, Sufian Radwan; Al-Slehat, Zaher Abdel Fattah; Al Sharif, Bader Mustafa; Aloshaibat, Sulieman Daood; Al-Haraisa, Yazan Emnawer; Almahasneh, Mohammad Abdlwhab (International Review of Management and Marketing, 2024)
This study aimed to analyze the relationship between financial literacy and mobile banking ‎usage, considering the moderating role of demographic characteristics among commercial ‎bank clients in the Jordanian southern provinces of Jordan. Using a sample of 1,380 commercial bank clients from ‎Jordan’s southern region. To achieve the study’s objective and test its hypotheses, the authors employed the quantitative method and utilized SPSS software version 28 for data analysis. The results revealed a strong positive relationship between ‎the level of financial literacy and mobile banking usage, with a moderating role of ‎demographic characteristics on the relationship between the level of financial literacy and ‎mobile banking usage. The study found that male clients and individuals with higher income levels were more inclined to utilize mobile banking services compared to female clients and those with lower income levels. On the other hand, age and educational level did not show a ‎moderating effect on this relationship. Based on the findings, the study recommends enhancing financial literacy through the development of programs and diverse digital banking products to meet client’s needs, thereby promoting the adoption of mobile banking services. ‎